Does controlled traffic have a place in high rainfall, undulating and difficult environments? - Russell, J.; Fisher, James; Murray-Prior, Roy; Pritchard, Deborah; Henson, Elizabeth; Eaton, John; Ashworth, M. (Australian Controlled Traffic Farming Association, 2007)
The sustainability of high production farming systems in the high rainfall Avon District of Western Australia is being investigated as a collaborative project between the Department of Agriculture and Food, Curtin University of Technology and the Western Australian No-Tillage Farmers Association. Paddock 30 at Curtin University’s Muresk Institute has been selected as the development site for this study with the approach of “putting the system back together”.A CTF system based on ‘multiple width tramlines’ was adopted in 2005 following initial paddockbenchmarking and analysis conducted the previous year. Detailed soil testing, radiometrics andanalysis of previous years’ yield maps have been used to identify zones of production. A tramline approach is seen as innovative in the district by local growers due to perceived constraints of topography, diverse soils and a medium to high rainfall environment. Investigations at the site currently focus on the practical elements of the cropping system in thisenvironment. The limitations to yield, the consequences of high production farming on the system and the impacts of management options on production, profitability and sustainability are being examined. In this paper, the progress of the first two seasons at Paddock 30 is described. Practical issues with the implementation of CTF and future activities planned for the site are discussed.